2017
DOI: 10.4172/2329-9002.1000178
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and Codon Usage of the Histone Genes in 12 Drosophila Species

Abstract: Histones are proteins that bind to DNA and form nucleosomes. There are several types of histones that differ in chromosome distribution and timing of their expression. In Drosophila, each canonical type histone is identical or highly similar in amino acid sequence to its corresponding replacement type histone; however, gene structure and codon usage differ between the two types of histones. Identification of the evolutionary changes responsible for the differences between these two histone types will lead to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…The positive relationship found between codon bias and the level of gene expression most likely resulted from the difference in translation efficiency [ 45 , 46 ]. Among the canonical histone genes, H2B showed the highest GC content at the third codon position, while H1 showed the lowest GC content at the third codon position [ 62 ]. H1, a linker protein, is expressed at approximately half of the level of the other four canonical histones.…”
Section: Evolution Of the Gc Content At The Third Codon Position Of The Histone Genes In Drosophilamentioning
confidence: 99%
See 4 more Smart Citations
“…The positive relationship found between codon bias and the level of gene expression most likely resulted from the difference in translation efficiency [ 45 , 46 ]. Among the canonical histone genes, H2B showed the highest GC content at the third codon position, while H1 showed the lowest GC content at the third codon position [ 62 ]. H1, a linker protein, is expressed at approximately half of the level of the other four canonical histones.…”
Section: Evolution Of the Gc Content At The Third Codon Position Of The Histone Genes In Drosophilamentioning
confidence: 99%
“…A comparison of the average GC content at the third codon position of genes in 12 common species revealed a higher GC content at the third codon position in the genes of the replacement type of histones than in those of the canonical type of histones [ 62 , 63 , 64 , 65 ]. Analysis of codon bias in the histone genes demonstrated that the difference was caused not by an obvious codon bias in a specific amino acid but by a general tendency that was observed for many codons [ 62 ]. Differences in functional differentiation or translation efficiency may be the cause of the differences in GC content at the third codon position between the histone types.…”
Section: Evolution Of the Gc Content At The Third Codon Position Of The Histone Genes In Drosophilamentioning
confidence: 99%
See 3 more Smart Citations